Gambaran Kondisi Fisik Sumur Gali di Tinjau dari Aspek Kesehatan Lingkungan dan Perilaku Pengguna Sumur Gali di Kelurahan Sumompo Kecamatan Tuminting Kota Manado - Katiho, Angela Suryani; Joseph, Woodford B. S.; Malonda, Nancy S. H. (Sam Ratulangi University, 2012)
The dug well is one of the sources of water supply for communities in rural and urban areas. The dug well as water sources must be compatible with the requirements laid down between the physical condition of the dug well in which the terms related to the construction of wells and the location of wells to the sources of pollutants, so that the water from the wells is safe for healthy to consumption. 1. To describe the physical condition of The dug well include construction, distance latrine to the dug well, and distance from the source of other pollutants such as cattle sheds and a pool of water; 2. To determine the behavior of resident user about the physical condition of the dug well, including knowledge, attitudes and actions. This study is a descriptive survey in which the population was divided into the dug wells population which amount 20 dug well and the dug well resident user behavior population which amounts to 125 respondents. Observation the dug well were using a checklist as an instrument of research and user behavior were using questionnaires. The physical condition of all the dug well 100% does not fulfill the requirements, which based on the construction of the dug well, distance the dug well to the latrine, the distance to the cattle sheds and a pool of water as a source of other pollutants. Based on user aspects of dug well; 78% of respondents knowledgeable well, 22% less; 74% have a good attitude, 26% less, and 32% had good action, 68% less. From the results of this study researchers to grant suggestion as good as posible to repair the physical condition of the dug well, to do espionage to the resident user the dug well about the physical condition of the dug well, there is a need for monitoring and surveillance of water quality, and should to involve to society independently of absolute needs clean water.Â ABSTRAKSumur gali merupakan salah satu sumber penyediaan air bersih bagi masyarakat di pedesaan, maupun perkotaan. Sumur gali sebagai sumber air bersih harus ditunjang dengan persyaratan yang ditetapkan diantaranya kondisi fisik sumur gali yang didalamnya menyangkut syarat konstruksi sumur dan lokasi sumur dengan sumber pencemar, agar air sumur aman bagi kesehatan untuk di konsumsi. 1. Untuk menggambarkan kondisi fisik sumur gali meliputi konstruksi sumur gali, jarak jamban dengan sumur gali dan jarak sumber pencemar lain seperti kandang ternak dan genangan air dengan sumur gali; 2. Untuk mengetahui perilaku pengguna sumur gali tentang kondisi fisik sumur gali meliputi pengetahuan, sikap dan tindakan. Penelitian ini bersifat survei deskriptif dimana populasi dalam penelitian ini terbagi menjadi populasi sumur gali yakni 20 sumur gali dan populasi perilaku pengguna sumur gali yang berjumlah 125 responden. Pengamatan sumur gali ini menggunakan checklist sebagai instrumen penelitian sedangkan perilaku pengguna sumur gali menggunakan kuesioner.Hasil penelitian menunjukkan bahwa kondisi fisik pada semua sumur gali 100% tidak memenuhi syarat, yakni berdasarkan konstruksi sumur gali, jarak dengan jamban, jarak dengan kandang ternak dan genangan air sebagai sumber pencemar lain. Berdasarkan aspek pengguna sumur gali ; 78% responden berpengetahuan baik, 22% kurang ; 74% memiliki sikap yang baik, 26% kurang ; dan 32% memiliki tindakan yang baik, 68% kurang. Dari hasil penelitian ini peneliti memberikan saran perlunya perbaikan kondisi fisik sumur gali, perlu dilakukan penyuluhan kepada masyarakat pengguna sumur gali tentang kondisi fisik sumur gali, perlu adanya pemantauan dan pengawasan kualitas air bersih, dan sebaiknya melibatkatkan masyarakat agar masyarakat secara mandiri memenuhi kebutuhan mutlak yakni air bersih.